DEVELOPMENT OF A NON-TEXTBOOK BASED ON THE CHARACTERIZATION OF PITCHER PLANTS (NEPENTHES SP.) IN NORTH SUMATRA AS A MEDIA TO IMPROVE KNOWLEDGE - Nainggolan, Letti (Universitas Negeri Medan, 2025)
This research aimed to develop a non-textbook on the characterization of pitcher plants (Nepenthes sp.) in North Sumatra as an alternative educational media and knowledge enrichment source for the general public. The research employed a Research and Development (R&D) approach using the 4D model (define, design, develop, disseminate) to systematically identify user needs, design content, validate the product, and evaluate its effectiveness. Field data were collected from six regencies in North Sumatra, involving morphological observations of 37 characters with 72 sub-characters across various species. The developed non-textbook, Exploring the World of North Sumatran Pitcher Plants, comprises 120 pages with carefully designed layout, typography, and illustrations. Expert validation across content, language, presentation, and graphic aspects indicated that the book met high-quality standards. A limited-scale trial with 20 general public participants further confirmed its feasibility, with an average assessment score of 85.11 (excellent). During dissemination, 60 participants from Medan, the research regencies, and North Sulawesi underwent a pretest–posttest evaluation, showing a substantial increase in knowledge, with an average N-gain of 1.37 (high). The research demonstrates the effectiveness of the developed non-textbook in enhancing public understanding of Nepenthes species while promoting biodiversity literacy and conservation awareness.